The Importance of The Minimum Limitation of Criminal Proof as The Implementation of The Unus Testis Nullus Testis Principle In Court - Lase, Albert Michael Julyan (Andalas Law Journal, 2023)
The main requirements in proving a criminal case must be based on valid evidence according to law and the judge's conviction on deciding a case. In the practice of the criminal justice system, there is often a lack of accuracy by judges in deciding a case, so unclear cases are still decided guilty by judges. That was only the accused's statement that proved the criminal act. What is the regulation regarding the minimum limit for proving a crime as a strength of the accused's statement as evidence of a crime in terms of the unus testis nullus testis? The imposition of decisions for perpetrators of criminal acts is regulated in Article 183 of the Criminal Procedure Code. However, there is no minimum limit for judges to consider proving a crime. Based on Article 189 (4) of the Criminal Procedure Code, the accused's statement is insufficient to prove a crime. This is because the interpretation of the article could be more precise. However, in practice, the accused's testimony has been used as the only evidence in deciding the accused's guilt in a criminal case in an Indonesian court. So, a minimum limit is needed in proving a criminal case. Criminal law as an ultimum remedium is not used arbitrarily by law enforcers and guarantees the protection of citizens' human rights as the goal of criminal law.